Real-World Study of Multiple Naloxone Administrations for Opioid Overdose Reversal among Emergency Medical Service Providers. Issue 1 (December 2022) - Abdelal, Randa; Banerjee, A. Raja; Carlberg-Racich, Suzanne; Cebollero, Christopher; Darwaza, Neyla; Kim, Chong; Ito, Diane; Epstein, Josh
Background : The increasing rates of highly potent, illicit synthetic opioids (i.e., fentanyl) in the US is exacerbating the ongoing opioid epidemic. Multiple naloxone administrations (MNA) may be required to successfully reverse opioid overdoses. We conducted a real-world study to assess the rate of MNA for opioid overdose and identify factors associated with MNA. Methods : Data from the 2015–2020 National Emergency Medical Services Information System was examined to determine trends in events requiring MNA. Logistic regression analysis was performed to determine factors associated with MNA. Results : The percentage of individuals receiving MNA increased from 18.4% in 2015 to 28.4% in 2020. The odds of an event requiring MNA significantly increased by 11% annually. The adjusted odds ratio (aOR) for MNA were greatest among males, when advanced life support (ALS) was provided, and when the dispatch complaint indicated there was a drug poisoning event. Conclusions : The 54% increase in MNA since 2015 parallels the rise in overdose deaths attributable to synthetic opioids. This growth is visible in all regions of the country, including the West, where the prevalence of illicitly manufactured synthetic opioids is intensifying. Given this phenomenon, higher naloxone formulations may fulfill an unmet need in addressing the opioid overdose crisis.